Solving an Integrated Project Portfolio Selection and Contractor Selection Problem: Fuzzy Goal Programming Based on Fuzzy Preference Relations - Zahedirad, Mostafa; Khalili-Damghani, Kaveh; Ghezavati, Vahidreza; Komijan, Alireza Rashidi (Fuzzy information and engineering, 2025)
Several factors affect the flexibility and the complexity of the project selection and the contractor selection problems. Project portfolio managers are expected to select the best combination of projects and contractors considering multiple conflicting objectives in a multi-period planning horizon. In this paper, we propose an integrated project portfolio optimization and contractor selection problem. The problem is modeled through a multi-objective Mixed Integer Linear Programming (MILP) model. Three solution approaches including Goal Programming (GP), Fuzzy Goal Programming (FGP), and fuzzy goal programming considering a fuzzy preference relationship are proposed. All solution approaches have been applied to a real case. The computational results show the out performance of FGP considering fuzzy relations. The time complexity of the proposed models in the sense of the relation of CPU time and the number constraints and variables of the models were discussed.